Mechanisms of Cryptococcus neoformans-Mediated Host Damage - Casadevall, Arturo; Coelho, Carolina; Alanio, Alexandre (Frontiers in Immunology, 2018)
Cryptococcus neoformans is not usually considered a cytotoxic fungal pathogen but there is considerable evidence that this microbe can damage host cells and tissues. In this essay, we review the evidence that C. neoformans damages host cells and note that the mechanisms involved are diverse. We consider C. neoformans-mediated host damage at the molecular, cellular, tissue and organism level. Direct mechanisms of cytotoxicity include lytic exocytosis, organelle dysfunction, phagolysosomal membrane damage and cytoskeletal alterations. Cytotoxicity contributes to pathogenesis by interfering with immune effector cell function and disrupting endothelial barriers thus allowing dissemination. When C. neoformans-mediated and immune-mediated host damage is sufficient to affect homeostasis, cryptococcosis occurs at the organism level.